Evidence of parasexual exchange of DNA in the rice blast fungus challenges its exclusive clonality - Zeigler, R.S.; Scott, R.P.; Leung, H.; Bordeos, A.A.; Kumar, J.; Nelson, R.J. (Scientific Societies, 1997)
We applied DNA markers to determine whether parasexual recombination may contribute to the extreme genetic diversity and variability observed in Magnaporthe grisea, the causal agent of rice blast disease. Dispersed repetitive elements and mapped, low-copy restriction fragment length polymorphism (RFLP) probes were used to detect transfers of DNA between cultured isolates of M. grisea. Low-copy RFLP probes also were used to detect putative recombinants among isolates from well-characterized field populations of the pathogen. Microscopic examination of tufted mycelium between cocultured isolates revealed frequent hyphal fusions. Hyphal tips and conidia were recovered without selection from tufted zones in two separate vegetative pairings involving isolates with dissimilar haplotypes, based on the repetitive element MGR586. Haplotypic changes were observed at a higher frequency in tuft derivatives than in subcultures of each isolate alone. From 136 tuft derivatives analyzed, 5 putative recombinant haplotypes were identified. Introgression was demonstrated with two independent repetitive elements, fosbury and MGR586, as probes on DNA digested with several restriction enzymes. Introgressions were characterized by addition of 1 to 10 MGR586 bands, and 1 to 3 fosbury bands from one parent into the background of the other. Polymorphic single-copy probes were used to analyze putative recombinants. One probe detected an introgression event as predicted by analysis with MGR586. To assess the possible role of parasexual recombination in field populations of the pathogen, isolates in the Philippines previously grouped based on DNA fingerprinting were analyzed with low-copy RFLP markers. Polymorphism in single-copy loci typically was seen between, but not within, putative pathogen lineages. One lineage (designated lineage 4), however, was polymorphic for several probes. For some isolates, alleles at these loci comigrated with alleles characteristic of other lineages, suggesting the transfer of DNA fragments between lineages. One isolate was apparently a merodiploid, carrying an allele typical of lineage 4 plus another allele characteristic of a different lineage. In a survey of isolates from the Indian Himalayas, a merodiploid also was found with single- or low-copy probes. Examination of MGR586 profiles of the putative recombinant and its putative donor strains showed the expected introgression of MGR586 bands. The detection of parasexual DNA exchanges in wild-type strains under unselected conditions and the existence of merodiploids in nature suggest that parasexual recombination occurs in field populations of M. grisea. This raises questions concerning exclusive clonality in the blast fungus.